Improved Cell Selectivity of Pseudin-2 via Substitution in the Leucine-Zipper Motif: In Vitro and In Vivo Antifungal Activity - Park, Seong-Cheol (Antibiotics (Basel), 2020)
Several antimicrobial peptides (AMPs) have been discovered, developed, and purified from natural sources and peptide engineering; however, the clinical applications of these AMPs are limited owing to their lack of abundance and side effects related to cytotoxicity, immunogenicity, and hemolytic activity. Accordingly, to improve cell selectivity for pseudin-2, an AMP from Pseudis paradoxa skin, in mammalian cells and pathogenic fungi, the sequence of pseudin-2 was modified by alanine or lysine at each position of two amino acids within the leucine-zipper motif. Alanine-substituted variants were highly selective toward fungi over HaCaT and erythrocytes and maintained their antifungal activities and mode of action (membranolysis). However, the antifungal activities of lysine-substituted peptides were reduced, and the compound could penetrate into fungal cells, followed by induction of mitochondrial reactive oxygen species and cell death. In vivo antifungal assays of analogous peptide showed excellent antifungal efficiency in a Candida tropicalis skin infection mouse model. Our results demonstrated the usefulness of selective amino acid substitution in the repeated sequence of the leucine-zipper motif for the design of AMPs with potent antimicrobial activities and low toxicity.